Negro barber, Barbados - Weatherhead, Bruce (My University, 2018)
A barber in Barbados is seen carrying out his trade by the side of the street, while his client reads the newspaper. Behind them a man can be seen sitting looking on, while smoking a pipe. The "Barber" sign is also most visible. Information at the back: Published by Bruce Weatherhead, Barbados Pharmacy
Landscape; black and white, 4 x 6 in.
Keywords: Barbers; Barbering; Smokers; Smoking; Cutting hair; Hair cut